SISTEM KELISTRIKAN PADA KAPAL PERANG TNI AL KELAS FROSCH KRI TELUK CELUKAN BAWANG 532 - Redaksi Tim Jurnal (Energi & Kelistrikan, 2017)
A warship has its own power plant which directly supply and distribute to meet its electrical power demand. On a warship which operated by Satuan Amphibi Komando Armada Republik Indonesia Kawasan Barat TNI AL, KRI Teluk Celukan Bawang 532 has 4 diesel generators located in engine room. This 4 diesel generators have a parallel connection and alternately work with the change of electrical load. The change of electric load based on a warship operating conditions. Power supply on the warship needs to generate and maintain a constant electric voltage and frequency, as well as a sufficient power when a warship is docking, before sailing and sailing. A calculation of elecric loads is very important to choose the capacity and the number of generator used with limitedspace on a warship.